COVID-19: lessons from paediatric population and primary immunodeficiency - Ismail, Intan Hakimah (Universiti Putra Malaysia, 2020)
Coronavirus timeline: In late December 2019, the Health Officials in Wuhan, China reported a cluster of pneumonia cases of unknown aetiology with a common link of being exposed to the Hunan Seafood Market in Wuhan [1]. This has raised an intense attention not only within China but also internationally as the world watched closely of what would be the cause and how bad it will be. Later, on 7 January, it was officially announced by the World Health Organisation (WHO) that the culprit of this outbreak was a new strain of virus that has not been previously identified or detected in humans, named novel coronavirus (2019-nCOV), and then renamed SARS-CoV-2 [1]. This new virus belongs to the same coronavirus family as severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERSCoV) that caused outbreaks in China and Saudi Arabia, respectively. The disease, named coronavirus disease 2019 (COVID-19), subsequently spread globally leading to the pandemic declaration by the WHO on March 11, 2020 [2]. The numbers continue to escalate daily; until this article was written, there were over 56 million confirmed cases resulting in more than 1.3 million deaths were reported worldwide. COVID-19 poses a global serious threat to human life and health welfare. When we first here about this outbreak, I believe majority of Malaysians would never in our wildest dream imagine that the virus could be tracked down in Malaysia. The first three COVID-19 cases in Malaysia was reported among tourists from China in Johor Bahru on 25 January, and the first two deaths was recorded on 17 March [3]. As of November 19th, a total of 51,680 positive COVID-19 cases and 326 deaths were reported in Malaysia.